Personalidades negras: trajetórias, visibilidade e representatividade - Costa, Robson Pedrosa (Afro-Ásia, 2022)
Resenha de: GOMES, Flávio dos Santos; LAURIANO, Jaime; SCHWARCZ, Lilia Moritz. Enciclopédia Negra. São Paulo: Companhia das Letras, 2021. 687 p.